Technological Innovations and Workers' Job Insecurity: The Moderating Role of Firm Strategies - Mauro Caselli; Andrea Fracasso; Arianna Marcolin; Sergio Scicchitano (Center for Economic Studies and ifo Institute (CESifo), 2023)
In this paper, we empirically assess whether the perceived implications of technological innovations on the probability of job loss vary according to the innovation-related strategies adopted by firms. We take advantage of a unique dataset based on a large and representative cross-sectional survey covering several characteristics of Italian workers and their firms. We find that the relationship between technological innovations and job insecurity is moderated by firms' technology-specific training programs, their dismissal plans, and the impact of innovations on the tasks and activities performed by workers. Thus, workers' perceptions of job insecurity vary significantly across innovative firms and the adoption of technological innovations in the workplace has a multifaceted impact on the perceptions of job insecurity of the affected workers.
Keywords: J28; O33; 330; job insecurity; technology; innovation; firms